Implementation of Electronic Medical Records Using the Technology Acceptance Model (TAM) Method at Lavalette Hospital Malang - Kirana, Erinia Rahayu Okta; Rusdi, Achmad Jaelani; Ma'ruf, Agus Sukron (Universitas Ibn Khaldun Bogor, 2025)
The development of technology is very rapid, especially in the health sector, namely in the use of RME (Electronic Medical Records), one of the hospitals that runs RME is Lavalette Hospital Malang. The implementation of RME at Lavalette Hospital Malang uses the TAM (Technlogy Acceleration Model) method, which is by paying attention to five important constructs, including perceived ease of use (PEOU), perceived usefulness (PU), attitude toward using (ATU), behavioral intention to use (BIU), and actual system usage (ASU). This aims to evaluate the acceptance rate of RME by health workers such as medical record heads, medical record officers, doctors, nurses, and even IT (Information Technology) officers with a focus on ease of use, usability, attitude towards use, intention to use, and actual use of the system. Methods: This type of research is qualitative research with a descriptive approach through structured interviews and participatory observations. Results: The results of the study show that the implementation of RME at Lavalette Hospital Malang has a positive impact on productivity and ease of work, although there are obstacles in implementation such as system errors and training needs. This research is expected to provide recommendations for the improvement of the RME system in hospitals as well as practical benefits for health and educational institutions. Conclusion: The RME switch at Lavalette Hospital Malang has shown good progress because it has been integrated by the installations there. However, for its optimization, periodic evaluations are needed.